Association between positive urine cultures and necrotizing enterocolitis in a large cohort of hospitalized infants. Issue 10 (October 2015) - Pineda, Leslie C.; Hornik, Christoph P.; Seed, Patrick C.; Cotten, C. Michael; Laughon, Matthew M.; Bidegain, Margarita; Clark, Reese H.; Brian Smith, P.
Abstract Objective We used a large research database to examine the association between urinary tract infections and necrotizing enterocolitis (NEC) in premature infants. Methods This retrospective data analysis included infants ≤ 32 week gestational age and ≤ 1500 g at birth who had urine cultures obtained at one of 322 neonatal intensive care units managed by the Pediatrix Medical Group from 1997 to 2012. The primary outcome was a diagnosis of NEC within 7 days after urine culture. We used multivariable conditional logistic regression conditioned on postnatal age and controlling for gestational age, inotropic support on the day of culture, and mechanical ventilation on the day of culture to evaluate the association between urine culture result and NEC. Results We identified 25, 816 infants who had 43, 556 urine cultures obtained; 6586 (15.1%) of the cultures were positive. A diagnosis of NEC within 7 days after culture was made in 334 (5.1%) of the 6586 positive cultures versus 1582 (4.3%) of the 36, 970 negative cultures (p < 0.01). On multivariable analysis, infants with any positive urine culture had increased risk of NEC (odds ratio [OR] 1.16, 95% confidence interval [CI] 1.02–1.31); the risk was higher when limited to Gram-negative organisms (OR 1.37, 95% CI 1.17–1.59). The risk of surgical NEC was increased in infants with any positive urine culture (OR 1.46, 95% CI 1.18–1.81) and was also higher when limited to Gram-negative organisms (OR 1.99, 95% CI 1.53–2.59). Conclusion Positive urine cultures were associated with increased risk of NEC within 7 days of culture.